PENGGANTIAN BENDA WAKAF TATKALA RUSAK ATAU TIDAK BERMANFAAT: ANALISIS KOMPARATIF FIKIH ISLAM DAN KOMPILASI HUKUM ISLAM (KHI) - Mukhlis Ali, Abdan; La Harisi, Isnaini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Istibdal waqf refers to the replacement of endowed property that is damaged, unfit, or has lost its relevance to the original purpose. According to data from the Indonesian Waqf Board (BWI), over 4,000 plots of waqf land in Indonesia remain unproductive, indicating an urgent need for an appropriate legal solution. This study aims to comparatively analyze the perspectives of the four major Islamic legal schools Hanafiyyah, Malikiyyah, Shafi‘iyyah, and Hanabilah with the prevailing national legal frameworks, particularly the Compilation of Islamic Law (KHI) and Law Number 41 of 2004 on Waqf. The study adopts a normative qualitative approach using library research and legal content analysis through a normative-comparative matrix. The analysis includes eight relevant articles from KHI and the Waqf Law, as well as ten authoritative classical fiqh sources. The findings reveal that all four schools permit istibdal under certain conditions: Hanafiyyah tends to be permissive, Malikiyyah selective, Shafi‘iyyah highly restrictive, and Hanabilah moderate. While KHI and the Waqf Law do not explicitly mention the term “istibdal,” they establish a strict legal mechanism requiring the approval of the Religious Court and recommendations from BWI. This study integrates the principles of maslahah (public benefit) and donor intent in fiqh with legal certainty and accountability in positive law, forming an adaptive and accountable waqf management model. Its main contribution is the formulation of a normative-applicative evaluation framework that can serve as a practical guide for nazhir (waqf managers), BWI, and the Religious Courts in making lawful, transparent, and benefit-oriented istibdal decisions. ABSTRAK Istibdal wakaf adalah mekanisme penggantian harta wakaf yang rusak, tidak layak, atau kehilangan relevansi terhadap tujuan awal. Berdasarkan data Badan Wakaf Indonesia (BWI), lebih dari 4.000 bidang tanah wakaf di Indonesia masih tidak produktif, menunjukkan kebutuhan mendesak akan solusi hukum yang tepat. Penelitian ini bertujuan menganalisis secara komparatif pandangan empat mazhab fikih utama Hanafiyah, Malikiyah, Syafi’iyah, dan Hanabilah dengan regulasi hukum positif, khususnya Kompilasi Hukum Islam (KHI) dan Undang-Undang Nomor 41 Tahun 2004. Pendekatan yang digunakan adalah kualitatif normatif dengan metode studi pustaka dan teknik analisis konten hukum melalui matriks analisis normatif-komparatif. Kajian dilakukan terhadap delapan pasal dalam KHI dan UU Wakaf serta sepuluh sumber fikih klasik. Hasil menunjukkan bahwa semua mazhab membolehkan istibdal dalam kondisi tertentu: Hanafiyah cenderung permisif, Malikiyah selektif, Syafi’iyah sangat restriktif, dan Hanabilah moderat. KHI dan UU Wakaf, meskipun tidak menyebut istilah